Survey of the Relationship between Fatty Liver Disease in Men by Ultrasound and Serum Ferritin Level - Saeedi, Amin; Rezaiye, Milad; Saeed, Fatemeh; Raesi, Rasoul; Raei, Mehdi; Farahbakhsh, Salman; Daneshi, Salman (Archives of Advances in Biosciences, 2023)
Introduction: The most common hepatic disease is fatty liver. Raised serum ferritin levels are often described as an indicator of liver function. The present study aimed to evaluate the correlation between fatty liver in men by ultrasound and serum ferritin levels in patients referred to Imam Khomeini Hospital in Jiroft in 2020. Materials and Methods: In this case series study, there is both a descriptive and an analytical component. The study population consisted of all male patients with fatty liver. Patients were included in the study after being visited by a specialist and thus diagnoses their fatty liver were mades by ultrasound. After clinical examination and diagnosis of fatty liver, patients were prepared on a fasting basis for Paraclinical tests (serum levels of iron, and ferritin). After collecting data from patient surveys based on a researcher-made checklist, the data were entered into SPSS V23 (22). Results: The mean age of patients was 46.8± 16.7. 27. There was a statistically significant correlation between ferritin level and disease severity based on the ultrasound view (P-value = 0.000). Also, there was a significant correlation between serum iron level and disease severity based on the ultrasound view (P-value = 0.005). Conclusion: The present study findings indicate a correlation between the severity of fatty liver disease and the level of serum ferritin and iron. Therefore, we need to pay special attention to the level of these indicators in patients with fatty liver.